Bipolar Switching Characteristics of RRAM Cells with CaBi4Ti4O15 Film - Jian-Yang Lin; Chia-Lin Wu (Advances in Materials Science and Engineering)
The electrical conduction and bipolar switching properties of resistive random access memory (RRAM) cells with transparent calcium bismuth titanate (CaBi4Ti4O15—CBTi144) thin films were investigated. Experimentally, the (119)-oriented CBTi144 thin films were deposited onto the ITO/glass substrates by RF magnetron sputtering followed by rapid thermal annealing (RTA) at a temperature range of 450–550°C. The surface morphologies and crystal structures of the CBTi144 thin films were examined by using field-emission scanning electron microscopy and X-ray diffraction measurements. The on/off ratio and switching behaviors of the transparent Al/CBTi144/ITO/glass RRAM devices were further discussed in this work.